Literaturoznawcza recepcja twórczości Andrzeja Płatonowa w Polsce - Witowicz, Bożena (Przegląd Rusycystyczny, 2009)
ЛИТЕРАТУРОВЕДЧЕСКАЯ РЕЦЕПЦИЯ ТВОРЧЕСТВА АНДРЕЯ ПЛАТОНОВА В ПОЛЬШЕ Резюме В статье дается обзор работ польских литературоведов по творчеству Андрея Пла тонова. Сначала обсуждаются общие методологические проблемы изучения русской литературы (первой половины) XX века, затем авторы и основные темы литературоведческих трудов посвященных наследию Платонова в хронологическом порядке. В конце статьи упоминаются области творчества Платонова, которые пока не притянули научно-исследовательского внимания польских литературоведов. RECEPTION OF ANDREI PLATONOV’S WORKS BY POLISH LITERARY SCHOLARS Summary The article presents an outline of Polish literary research in the area of Andrei Platonov’s works. First, the paper focuses on general methodological diffi culties related to the research of Russian literature of (the fi rst half of) the 20th century, next it introduces authors and main subjects of their Platonov’s research presented in chronological order. In the end the author pinpoints those areas of Platonov’s works that until now have not received attention of Polish literary researchers.